Design and fabrication of newOrthoses to Preventing ankle equines in U shape ilizarov fixators - M. Arazpoor; M. Bahramizadeh; M. Mardani; M. Moosavi (Afarand Scholarly Publishing Institute, 2009)
Objective: The goal of this study was to design and manufacture a new type of foot orthosis that is used for preventing of equinus deformity of ankle complex in patient with ankle fracture or tibial lengthening by U shape Elizarov external fixator.     Material & Methods: In present discovery study after casting the patient's foot in neutral position, during afew steps orthosis that can joined to the U shape Elizarov external fixator, has been designed and manufactured.     Results: According to the results of this study, in new orthosis, the ankle complex will be in neutral position by joining the U shape Elizarov external fixator to it. The patient with orthosis can walk and his or her Activity daily living improve.   Conclusion: For the first time a new type of foot orthosis, for preventing of equinus deformity of ankle complex in patient that have to used U shape Elizarov, has been designed and manufactured.